2023
DOI: 10.1302/2046-3758.128.bjr-2022-0413.r2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of recurrence in limb osteomyelitis patients after antibiotic‐loaded cement spacer for definitive bone defect treatment

Hongri Wu,
Dong Sun,
Shulin Wang
et al.

Abstract: AimsThis study was designed to characterize the recurrence incidence and risk factors of antibiotic-loaded cement spacer (ALCS) for definitive bone defect treatment in limb osteomyelitis.MethodsWe included adult patients with limb osteomyelitis who received debridement and ALCS insertion into the bone defect as definitive management between 2013 and 2020 in our clinical centre. The follow-up time was at least two years. Data on patients’ demographics, clinical characteristics, and infection recurrence were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Importantly, the radiomics-based SVM model can identify these subtle features accurately, improving diagnotic accuracy. Our findings are consistent with the widely accepted perspective that eradicating osteomyelitis necessitates expanding the surgical scope (Lazzarini et al, 2002;McNally et al, 2022;Wu et al, 2023). Our results indicate that expanding the delineation range from 0 to 5 mm substantially enhanced MRI radiomics' diagnostic performance in osteomyelitis, providing valuable insights for osteomyelitis surgical scope guidance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, the radiomics-based SVM model can identify these subtle features accurately, improving diagnotic accuracy. Our findings are consistent with the widely accepted perspective that eradicating osteomyelitis necessitates expanding the surgical scope (Lazzarini et al, 2002;McNally et al, 2022;Wu et al, 2023). Our results indicate that expanding the delineation range from 0 to 5 mm substantially enhanced MRI radiomics' diagnostic performance in osteomyelitis, providing valuable insights for osteomyelitis surgical scope guidance.…”
Section: Discussionsupporting
confidence: 90%
“…KEYWORDS chronic osteomyelitis, radiomics, MRI, diagnostic accuracy, surgical decisionmaking, shape features, region of interest 1 Introduction Chronic osteomyelitis has long been recognized as one of the most challenging diseases in the medical field, often referred to as the "second cancer" (Zhang et al, 2019;Masters et al, 2022). Despite the refined antimicrobial activity of new-generation antibiotics and the efficacy of surgical intervention, the recurrence rate of chronic osteomyelitis remains as high as 20%-30% (Conterno and Turchi, 2013;Chastain and Davis, 2019;Zeitlinger, 2019;Wang X. et al, 2023).…”
mentioning
confidence: 99%
“…However, segmental bone defects are also a risk factor for infection recurrence. 34 Therefore, in these patients, it may be beneficial to consider using other methods for bone defect reconstruction. After radical debridement, it is necessary to stabilize the broken end of the bone defect to provide a stable environment for induced membrane formation and infection control.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have found that the risk factors for the recurrence of limb osteomyelitis infection treated with induced membrane technology include repeated surgery, post-traumatic osteomyelitis, and one-stage fixation ( Wang et al, 2020 ). In addition, previous studies have shown that segmental bone defects, Gram-negative bacterial infections, and smoking are risk factors for infection recurrence in patients with osteomyelitis treated with antibiotic bone cement spacers ( Wu et al, 2023 ). Different treatment methods have different risk factors for the recurrence of osteomyelitis infection.…”
Section: Discussionmentioning
confidence: 99%